A Review of Dimension in Human Capacity Development for Construction Projects - Azmi, Elmi Alif; Che Ibrahim, Che Khairil Izam (Online Journal for TVET Practitioners, 2023)
The ability of engineers to adapt and compete is crucial for the success and effectiveness of an organisation. Human capacity development (HCD) has been acknowledged as a concept to improve individual and team skills in setting goals and maintaining the competencies needed to survive and thrive in a rapidly changing world. Therefore, it is important to focus on HCD in order to strengthen engineers for long-term efficiency. Although previous studies have primarily focused on environmental and economic dimensions, the social dimension, specifically HCD, has received less attention. This paper aims to identify the attributes of HCD in sustainable construction during different phases of a construction project's life cycle. A systematic literature review was conducted to identify and critically evaluate papers related to HCD. The attributes identified as important for improved company or agency performance include Leadership, Knowledgeability and Accountability. Based on these findings, management initiatives to apply HCD can improve performance among civil engineers.